PENGARUH PERSEPSI MAHASISWA TERHADAP IMPLEMENTASI PROGRAM ASISTENSI MENGAJAR JURUSAN PENDIDIKAN EKONOMI UNIVERSITAS NEGERI GORONTALO - Siti Aisya; Radia Hafid; Maya Novrita Dama; Meyko Panigoro; Yulianti Toralawe (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The implementation of the Independent Learning-Independent Campus (MBKM) policy through the School Teaching Assistance Program faces challenges regarding students' adaptation readiness in partner schools. This study aimed to analyze the effect of students' perceptions on the implementation of the School Teaching Assistance Program (Batch 8) among Economic Education students, Class of 2022, at Universitas Negeri Gorontalo. This associative quantitative study involved 66 respondents selected through purposive sampling from a population of 192 students. Data were collected via structured Likert-scale questionnaires and analyzed using simple linear regression in SPSS version 29. The results revealed that students' perceptions had a positive and significant effect on program implementation (t_